The use of anterior segment optical coherence tomography (ASOCT) in demonstrating recurrence of vitreoretinal lymphoma (VRL) in the anterior vitreous - Vlad Diaconita; Heba Rihani; Virginia Mares; Marcio B. Nehemy; Sophie J. Bakri; Jose S. Pulido (International Journal of Retina and Vitreous, 2019)
Abstract Background Primary vitreoretinal lymphoma (VRL) is a rare disease with 30–380 new cases in the United States per year. Its insidious process and spread to the central nervous system (CNS) leads to a mean 5-year survival rate from 41.4 to 71%. Medical treatment of VRL has been summarized extensively in the literature and involves intraocular rituximab and methotrexate as first line agents in unilateral VRL, with systemic chemotherapy to be considered in bilateral or CNS-involving disease. In addition, therapeutic “debulking” vitrectomy has been reported in the literature, with some limited success. Despite this, recurrence rate is high and should always be suspected in the setting of new inflammation. Anterior segment optical coherence tomography (ASOCT) has not been previously used to image VRL recurrence in the anterior vitreous. Case presentation A 63-year-old man, with VRL was found to have cells and debris in the anterior vitreous, 10 months after his first vitrectomy, intravitreal rituximab and methotrexate. Since the patient was phakic at the time of initial vitrectomy, the anterior vitreous had not been removed. ASOCT confirmed the findings. Subsequent surgery removed the lens and debris. Both the patient’s vision and ASOCT improved. Conclusions We suggest that ASOCT of the anterior segment is a useful diagnostic tool to monitor for recurrence of VRL. In biopsy-proven VRL, phakic patients who undergo therapeutic vitrectomy, should also be considered for lens extraction and anterior vitrectomy to limit recurrences.